Pola Asupan Kolesterol Mingguan dan Kadar Kolesterol pada Lansia Posyandu Waras di Desa Krajan Kecamatan Gatak Kabupaten Sukoharjo - Mayasari, Setiyani Yenni; , Ririn Yuliati, S.SiT.,M.Si; , Elida Soviana, S.Gz., M.Gizi (2016)
Background: Cholesterol intake can affect cholesterol levels in the blood. The levels of food intake containing cholesterol can lead to the increase of cholesterol levels. In the elderly, increased levels of cholesterol can lead to atherosclerosis Objective : To determine the cholesterol intake weekly with cholesterol levels on the elderly at Posyandu Waras, Krajan village, Gatak district, Sukoharjo Research Method : This study was observational research with cross sectional approach. The amount of respondents were 46 people according to the inclusion criteria. Sampling method using consecutive sampling. Cholesterol intake data were obtained weekly for 4 times (4 weeks) with semi quantitative FFQ. Cholesterol levels were measured using spektrofotometer. The statistical test used were Kruskall Wallis and Pearson product moment. Result: The results the first week shows that respondents with good cholesterol intake was 60.9% and excess cholesterol intake was 39.1%. The second week results show that respondents with good cholesterol intake was 73.9% and excess cholesterol intake was 26.1%. Results of the third week showed that respondents with good cholesterol intake was 60.9% and excess cholesterol intake was 39.1%. The results of the fourth week showed that respondents with good cholesterol intake was 78.3% and excess cholesterol intake was 21.7%. The optimal cholesterol levels was 56.52%, 21.74% was on threshold and high cholesterol levels was 21.74%. There was no difference in cholesterol intake per week (p= 0.059). There was no difference in cholesterol weekly and cholesterol levels (p=0,167). Conclusion: There was no difference in cholesterol intake per week. There was no difference in cholesterol weekly and cholesterol levels Keyword : Cholesterol and cholesterol intake Literature : 48 : 2000 - 2014